Studying the Meaning of Cinematic Techniques Through Experimental Approach: Introducing the Semantic Spectrum Model - Soheil Seraji; Mostafa Goudarzi (هنرهای زیبا. هنرهای نمایشی و موسیقی)
This study introduces the semantic spectrum model for analyzing the meaning of cinematic techniques, proposing it as a more nuanced, precise, and comprehensive alternative to the conventional single-concept approach. The model suggests that the meanings of cinematic techniques should be understood as a spectrum, where multiple concepts coexist with varying degrees of emphasis rather than a definitive single interpretation. This framework accommodates the complex, often overlapping meanings that cinematic techniques can convey, offering a deeper and more flexible understanding of cinematic language.To test this hypothesis, an experimental approach was employed, involving a questionnaire based on selected cinematic techniques from two foundational texts: Cinematic Storytelling and Master Shots Vol. 3. The questionnaire included 17 cinematic techniques, split into two groups: one without a distractor option and one with a distractor option. The distractor was designed according to the semantic spectrum model, representing a meaning closely related to, but distinct from, the expected answer, which was based on the text of the two books, thus testing the audience's tendency toward diverse interpretations.Sixty-nine participants responded to the questionnaire, and their answers were analyzed to determine whether the semantic spectrum model better represented how audiences interpret cinematic techniques. The findings revealed that the distractor options, representing the semantic spectrum model in the second group, attracted 33% of responses—a significant portion of the audience. Furthermore, 13% of those who selected the expected answer in the first group and 20% who chose other options shifted to the distractor option in the second group, suggesting a preference for more nuanced interpretations when available.The study also noted that audience preference for options which were expected to attract more responses—46% in the first group (for the expected answer) and 66% in the second group (for both the expected answer and the distractor)—suggests that when presented with a spectrum of possible meanings, audiences are more likely to consider and engage with multiple interpretations. This reflects the model’s effectiveness in capturing the complexity of cinematic meanings. The results indicate that a spectrum-based approach can significantly enrich our understanding of cinematic language by revealing the layered nature of audience interpretation.These findings highlight the challenges of drawing strict boundaries between the meanings attributed to cinematic techniques and question the adequacy of single-concept interpretations. The semantic spectrum model offers a more meaningful and accurate method for explaining the relationship between cinematic techniques and their meanings, allowing for the coexistence of multiple concepts with varying degrees of influence. This approach provides a more comprehensive understanding of how cinematic techniques can evoke layered interpretations and reflect the complexity of audience engagement with film language.In conclusion, the study demonstrates that the semantic spectrum model is an effective tool for analyzing cinematic meaning, with the potential to open new avenues for research in cinematic studies. The results encourage further exploration and application of this model, suggesting that each cinematic technique, when studied individually, holds substantial potential for deepening our understanding of cinematic meaning through experimental and quantitative methods, while fostering more nuanced interpretations.